The mediating role of the teacher in the face of the new paradigms of Higher Education - Dávila Matute, Feliciana del Socorro; Rodríguez Ruiz, Angelica María (Revista Multi-Ensayos, 2025)
The article presents an approach related to the mediating role of the higher education teachers in new educational paradigms, as these provide a basis for understanding, analyzing and developing learning through processes. Therefore, they are considered as models that are immersed in the different contexts, in the same way they are integrating all the educational agents. Higher education is transforming day by day, due to the emerging social changes including, climate change, gender equality, artificial intelligence, interculturality, inclusive education and emotional skills, which is closely related to emotional intelligence; Consequently there are curricular transformations. It is important for teachers to consider the evolutions of pedagogical processes, looking towards new dynamics, trends and potentialities, which allow preparing a scenario of reflection, understanding, as well as pertinent adaptations.